A preserved transseptal puncture zone in a novel PFO occluder enables safe repeat left atrial interventions: preclinical validation in a porcine model - Chen, Hao; Su, Yanlin; He, Ziqian; Wei, Yiting; Dang, Zihe; Cao, Suyan; Lu, Wenlin; Cao, Shaoqing; Yang, Chengjian; Jiang, Haibin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundConventional nickel-titanium patent foramen ovale (PFO) occluders hinder transseptal puncture due to septal obstruction, limiting access for left-heart interventions. To address this, we developed a modified PFO occluder with a designated puncturable zone.MethodsAn artificial PFO model was created in six pigs by puncturing and dilating the fossa ovalis. A novel PFO occluder preserving a central puncture area was implanted and validated intraoperatively via digital subtraction angiography (DSA) and transesophageal echocardiography (TEE). Transthoracic echocardiography and histology were performed 3 months post-implantation. Transseptal left atrial appendage closure (LAAC) was subsequently attempted through the occluder's puncturable zone.ResultsAll PFO closures were successful, with DSA/TEE confirming device stability. At 3 months, transseptal LAAC via the occluder's preserved area was achieved in all cases (6/6), validated by imaging. Histology revealed complete endothelialization of both occluders, intact nitinol framework, and precise puncture tracks within the designated zone without structural compromise.ConclusionThe novel PFO occluder with a dedicated puncture zone enables effective PFO closure while permitting safe transseptal access for subsequent left-heart interventions. This study demonstrates the occluder's feasibility, reliability, and clinical potential for aging populations requiring sequential cardiac procedures.